Serum‐free media supplements carry miRNAs that co‐purify with extracellular vesicles. Issue 1 (9th September 2019) - Auber, Martin; Fröhlich, Dominik; Drechsel, Oliver; Karaulanov, Emil; Krämer‐Albers, Eva‐Maria
ABSTRACT: Recent studies on extracellular RNA raised awareness that extracellular vesicles (EVs) isolated from cultured cells may co‐purify RNAs derived from media supplements such as fetal bovine serum (FBS) confounding EV‐associated RNA. Defined culture media supplemented with a range of nutrient components provide an alternative to FBS addition and allow EV‐collection under full medium conditions avoiding starvation and cell stress during the collection period. However, the potential contribution of serum‐free media supplements to EV‐RNA contamination has remained elusive and has never been assessed. Here, we report that RNA isolated from EVs harvested from cells under serum‐replacement conditions includes miRNA contaminants carried into the sample by defined media components. Subjecting unconditioned, EV‐free medium to differential centrifugation followed by reverse transcription quantitative PCR (RT‐qPCR) on RNA isolated from the pellet resulted in detection of miRNAs that had been classified as EV‐enriched by RNA‐seq or RT‐qPCR of an isolated EV‐fraction. Ribonuclease (RNase‐A) and detergent treatment removed most but not all of the contaminating miRNAs. Further analysis of the defined media constituents identified Catalase as a main source of miRNAs co‐isolating together with EVs. Hence, miRNA contaminants can be carried into EV‐samples even under serum‐free harvesting conditions using culture media that are expected to be chemically defined. Formulation of miRNA‐free media supplements may provide a solution to collect EVs clean from confounding miRNAs, which however still remains a challenging task. Differential analysis of EVs collected under full medium and supplement‐deprived conditions appears to provide a strategy to discriminate confounding and EV‐associated RNA. In conclusion, we recommend careful re‐evaluation and validation of EV small RNA‐seq and RT‐qPCR datasets by determining potential medium background.